Family Functioning and Attachment among Young Adults in Western and Non-Western Societies - Masoumeh Alavi,; Adibah Abdul Latif,; Mohd Tajudin Ninggal,; Mohamed Sharif Mustaffa,; Mansour Amini, (Routledge, 2020)
Family functioning (FF) is associated with patterns of adults’ close relationship attachment, which works differently in western and non-western societies. In this study, the relationship between FF and attachment (A), as well as the difference in relationship between FF and A across western and non-western societies were examined. A total of 600 young adults (294 males, 306 females) were recruited from western and non-western societies through the SurveyCircle and social media and communication applications. The data was analyzed using PLS-SEM and multigroup analysis, and the results showed that in western and non-western societies, family adaptability and cohesion were significantly associated with anxiety, close, and depend attachments. Unexpectedly, higher family adaptability was associated with higher anxiety attachment. The associations among family adaptability and cohesion with anxiety …